Language proficiency and personal journey. The case of Cape Verdeans in the archipelago and the Diaspora - (:unkn) unknown (My University, 2014)
Island state located off the Senegalese-Mauritanian coast, Cape Verde was inhabited from the late15th century by European settlers and African slaves. He inherited this story, a diglossic situationwhere Portuguese is the official language while Creole, now called « Cape Verdean language », -born of Luso-African language contacts – is the vehicle of everyday expression. The history of CapeVerdean society is also rooted in that of emigration and national and international mobility. If weatherconditions have prompted many Cape Verdean to exile, both in Africa than in Europe or the UnitedStates, structural handicaps have also favored the constant migrations of islanders worldwide.Through surveys conducted both in Cape Verde and France, are studied differences in languageproficiency between Cape Verdean who acquired their languages in each of these countries. Theanalysis is based primarily on their personal journeys and pays particular attention to the forms ofbilingualism of each other. The study, which focuses at first on Creole, Portuguese and French,include spontaneous and induced oral productions, and written productions, which are indicative oforal proficiency.
Keywords: African Research